P196 Healthcare utilisation by patients with Idiopathic Pulmonary Fibrosis; observations from the UK pirfenidone Named Patient Programme. (14th November 2013) - Parfrey, H; Leonard, C; Gibbons, MA; Armstrong, E; Harris, E; Frank, R; Sharp, C; Percival, F
Abstract : Introduction and Objectives: There are limited data on the healthcare resource use that arises as a consequence of idiopathic pulmonary fibrosis (IPF). Navaratnam et al 1 have recently reported rising hospital admissions due to IPF but utilisation of other health related services by individuals with IPF is unknown. As part of a real world assessment of the clinical experience of pirfenidone via the UK Named Patient Program data were collected to determine the burden placed on healthcare resources as a consequence of IPF. Methods: A multi-centre, retrospective, cohort review was undertaken across 4 NHS Trusts. Hospital resource use data were collected from the clinical records of individuals starting pirfenidone for IPF through the NPP before June 2012. Results: Data were available from 100 patients (76% male) at baseline and 67 through to nine months from baseline. At baseline, the mean ± S.D. age was 69.3 ± 7.5 years, mean ± S.D. FVC% predicted was 70% ± 19% and 62 patients were on oxygen therapy. In the first 6 months from baseline, 11 patients had 15 IPF-related hospitalisations of which 6 were for an acute exacerbation. One patient was hospitalised in the 6–9 months period. The mean ± S.D. and median (IQR) hospital bed days in the first 6 months were 11.0 ± 7.5 and 11.0 (6.0–13.5) days respectively for hospitalised patients and mean ± S.D. 1.2 ± 4.2 days for all patients. One patient was admitted to the Intensive Care Unit, for 5 days. Eighteen patients had IPF-related Accident and Emergency department visits, 3 had an IPF-related day-case and 67 outpatient clinic visits, with a mean of 2.1 ± 2.0 outpatient clinic visits per patient in the first 6 months of the observation period. Conclusion: IPF is a terminal disease associated with significant morbidity and mortality. This is reflected in the high level of resource use and frequent accessing of health care services by this severely ill cohort of patients. Whether resource use has been positively impacted by the introduction of pirfenidone is unknown but merits prospective assessment. Reference: Navaratnam V, Fogarty AW, McKeever T, Hubbard RB. The Increasing Secondary Care Burden of Idiopathic Pulmonary Fibrosis Hospital Admission Trends in England >From 1998 to 2010. CHEST 2013; 143(4):1078–1084